2006
DOI: 10.1063/1.2423235
|View full text |Cite
|
Sign up to set email alerts
|

Digitalized magnetoresistance observed in (La,Pr,Ca)MnO3 nanochannel structures

Abstract: Influence of structural disorder on magnetic and transport properties of ( La 0.7 Sr 0.3 ) 0.5 ( Pr 0.65 Ca 0.35 ) 0.5 MnO 3 films Low Temp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
(27 reference statements)
2
29
0
Order By: Relevance
“…However, submicrometer scale PS has also been observed in La 1ÿx Pr x Ca 0:375 MnO 3 (LPCMO) system where ferromagnetic (FM) metallic and charge ordered (CO) insulating domains coexist [13,14]. Although the driving mechanisms that cause large scale PS is still under investigation [15][16][17], the LPCMO system provides an ideal system for studying the effect of spatial confinement as it can be easily accessed by conventional lithographic fabrication processes [18,19]. In this work, we show never before observed emergent transport properties in LPCMO wires that differ vastly from bulk and thin films of the same material.…”
mentioning
confidence: 99%
“…However, submicrometer scale PS has also been observed in La 1ÿx Pr x Ca 0:375 MnO 3 (LPCMO) system where ferromagnetic (FM) metallic and charge ordered (CO) insulating domains coexist [13,14]. Although the driving mechanisms that cause large scale PS is still under investigation [15][16][17], the LPCMO system provides an ideal system for studying the effect of spatial confinement as it can be easily accessed by conventional lithographic fabrication processes [18,19]. In this work, we show never before observed emergent transport properties in LPCMO wires that differ vastly from bulk and thin films of the same material.…”
mentioning
confidence: 99%
“…Obtaining nanostructures of these materials is of paramount importance for realizing a highly integrated Fe-RAM device.The controlled nanofabrication of metal oxides is also important for the investigation of novel nanoscale properties. For example, Yanagisawa et al [4] have recently demonstrated that the resistivity of a ca. 500 nm wide perovskite (La, Pr, Ca)MnO 3 channel structure rapidly falls off over three orders of magnitude upon the application of a magnetic field, which is very different from the behavior of a large-area thin film.…”
mentioning
confidence: 99%
“…At this moment, the lower limit for the fine fabrication of oxides using photolithography is only ca. 1 lm, notwithstanding the remarkable advances in processing silicon surfaces with better than 100 nm resolution.Recently, there have been several reports in the literature dealing with the nanofabrication of transition metal oxides using top-down approaches such as focused ion beam (FIB) lithography, [5][6][7] atomic force microscopy (AFM) lithography, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and electron-beam (e-beam) lithography. [19,20] These methods have been used to achieve feature sizes less than ca.…”
mentioning
confidence: 99%
“…However, nanofabrication of oxide films is difficult. Currently, fabrication of oxide films with a lateral size smaller than %1 mm is very difficult by photolithography.Although there are many reports on the fabrication of oxide nanostructures, whose lateral sizes are as small as or less than several hundreds of nanometers, by atomic force microscopy (AFM), [5][6][7][8][9][10][11][12][13][14][15][16] focused ion beam (FIB), [17][18][19] and electron beam (EB)-based lithography techniques, [20][21][22][23][24] these methods are not suitable for large-area fabrication and mass production in industry. Nanoimprint lithography (NIL) is an emerging technology that enables fabrication of nanostructures as small as 10 nm.…”
mentioning
confidence: 99%